Energy Saving Through Development of New Copper Rotor of Induction Motor - Ismail, Daut, Prof. Dr.; Anayet, Karim; Gomesh Nair, Shasidharan; Syatirah, Mohd Noor; Mohd Asri, Jusoh; Mohd Muzhar, Ahmad Tajuddin (Malaysian Invention & Design Society (MINDS), 2010)
Prof. Dr. Ismail Daut and his team won silver at 21st International Invention, Innovation and Technology Exhibition (ITEX) 2010, 14th - 16th May 2010 di Kuala Lumpur Convention Centre (KLCC), Kuala Lumpur, Malaysia.